A descriptive study on the relationship between the behavioural dimension of consumer engagement and consumer purchase intention in a social media context. - de Koning, Rudolf (The IIE, 2019)
The ongoing positive effects of engagement on brands social media and its impact on consumers purchase intentions are motivating the academic and practical interest in influencing and explaining the concept. The study aims to identify the lack of understanding of how consumers’ engagement on brand-related content on social media is defined and how it correlates to a consumers purchase intention towards the brands product. Therefore the study described the behavioural dimension of consumer engagement consisting out of three sub-dimensions, learning, sharing and endorsing, and its relationship with consumers purchase intention on Facebook using the Freedom of Movement (FOM) brand as a case study. The primary research was done through the use of a cross sectional study. The data was collected through the use of 20 online questionnaires. The method was used as the study is descriptive of nature and aim to understand the relationship between two constructs. The method was also inexpensive and helped the researcher to collect a great deal of information quickly. Further did the findings of the study made it evident that there was no relationship between consumers engaging through sharing, learning and endorsing on the FOM Facebook page and their purchase intentions. The paper will contribute to the existing body of knowledge by explaining and investigating these constructs.
Keywords: Brand; Social media; Consumer behaviour; Consumer engagement; Buying behaviour